A World without Intellectual Property? A Review of Michele Boldrin and David Levine's Against Intellectual Monopoly - Gilbert, Richard (Journal of Economic Literature, 2011)
In their recent book, Against Intellectual Monopoly, Michele Boldrin and David Levine conclude that patents and copyrights are not necessary to provide protection for either innovation or creative expression and should be eliminated. The authors note the many flaws of the U.S. system of intellectual property protection and argue that other means are available to appropriate the benefits of invention and creative expression. While the authors overlook important functions of intellectual property, they provide support for further reforms of intellectual property law. (JEL K11, O31, O34)